2011
DOI: 10.2217/fon.11.43
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Prostate Cancer

Abstract: Prostate cancer is the most common malignancy in men, in general. Most patients diagnosed with prostate cancer have localized disease confined to the prostate. A small percentage of patients with aggressive tumors will progress to develop local, extracapsular tumor extension and distant metastases. The aim of prostate cancer management is to identify and treat those patients with aggressive disease before they develop locally advanced or metastatic disease, and to avoid overtreating indolent tumors, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Prostate cancer is the second most common cancer in men worldwide (almost 1.3 million diagnoses) and the fifth leading cause of cancer death among men (350,000 deaths worldwide) [159]. Furthermore, the increase in longevity and awareness of the disease is leading to more men requesting screening, which in turn will dramatically increase the number of patients diagnosed [160]. Barr et al [161] provided an extensive study of guidelines and recommendations on the clinical use of ultrasound elastography on the prostate.…”
Section: Prostatementioning
confidence: 99%
“…Prostate cancer is the second most common cancer in men worldwide (almost 1.3 million diagnoses) and the fifth leading cause of cancer death among men (350,000 deaths worldwide) [159]. Furthermore, the increase in longevity and awareness of the disease is leading to more men requesting screening, which in turn will dramatically increase the number of patients diagnosed [160]. Barr et al [161] provided an extensive study of guidelines and recommendations on the clinical use of ultrasound elastography on the prostate.…”
Section: Prostatementioning
confidence: 99%
“…TRUS was traditionally used to allow biopsies from predetermined sites in the prostate, following an abnormal digital rectal examination (DRE) and increased PSA, and not as a method to identify precise locations of tumour foci [82]. However, improvements to the technique, including contrast-enhanced ultrasound using microbubble contrast media, elastography to measure tissue stiffness, and Doppler ultrasound to measure blood flow, can result in more targeted biopsies, leading to improved detection and diagnosis [83, 84].…”
Section: Approaches To Focal Therapy Of Localized Prostate Cancermentioning
confidence: 99%
“…However, improvements to the technique, including contrast-enhanced ultrasound using microbubble contrast media, elastography to measure tissue stiffness, and Doppler ultrasound to measure blood flow, can result in more targeted biopsies, leading to improved detection and diagnosis [83, 84]. TRUS can distinguish between an outer and inner gland encompassing the central, peripheral, and transition zones, though not at the same resolution as MRI [82]. …”
Section: Approaches To Focal Therapy Of Localized Prostate Cancermentioning
confidence: 99%
“…Furthermore, over 80% of PCas are multifocal, which makes accurate clinical staging even more difficult and unreliable 7 . Clinical tumour understaging has consistently been shown to range from 40% to 60% 8–11 . This is clearly attributable to the multifocal, histologically heterogeneous nature of prostatic carcinoma.…”
Section: Clinical Staging Versus Pathological Stagingmentioning
confidence: 99%
“…7 Clinical tumour understaging has consistently been shown to range from 40% to 60%. [8][9][10][11] This is clearly attributable to the multifocal, histologically heterogeneous nature of prostatic carcinoma. Bostwick et al found that 59% of clinical stage T2, T3 and T4 PCas in men undergoing radical prostatectomy were understaged when compared with final pathological stage.…”
Section: Clinical Staging Versus Pathological Stagingmentioning
confidence: 99%